JARINGAN KOMUNIKASI DI USAHA KECIL DAN MENENGAH TRIS FLOWER JAMBANGAN SURABAYA - Angela, Thevani Clarine; S. F, Brigitta Revia; Nugraheni, Yuli (Universitas Muhammadiyah Jember, 2020)
This study aims to determine the communication network at Small and Medium Enterprises Tris Flower Jambangan Surabaya which has a waste recycling management process that is sorting raw materials, cleaning or washing, designing models, cutting materials and sewing. This study explains the process of forming a communication network that starts from two-way communication and then develops into reciprocal communication so that it can form a convergence communication model. This study uses a network analysis method, which aims to assist researchers in making a relationship map (mapping) through a matrix and sociogram. Through this sociogram we can know the role of the network including Components, Clicks, Bridges, Hubs, Cutpoints, Isolates. The results of this study are the roles that appear in the waste recycling processing network namely; (1) sorting raw materials there are roles of Clicks, Cutpoints, Bridges , and Hubs, (2) cleaning and washing, there is the role of Hubs, (3) designing models or designs there are roles of Clicks, Isolate, Cutpoints, and Hubs, (4) cutting of materials there is the role of Clicks, Cutpoints, and Hubs, (5) sewing there is the role of Isolate, and Hubs.